An integrative review of sport-based youth development literature - Jones, Gareth J.; Edwards, Michael B.; Bocarro, Jason N.; Bunds, Kyle S.; Smith, Jordan W. (Sport in society, 2017)
Sport is frequently regarded as an effectual mechanism for promoting positive youth development (PYD). However, this connection is not inherent, and depends upon a variety of programmatic and contextual factors. To help elucidate these linkages, scholars have called for more process-based approaches to programme evaluation and research. This paper contributes to that agenda by presenting the results of a systematic integrative review of the empirical sport-based PYD literature. Using a theory of change to guide coding and analysis, these findings demonstrate how various aspects of the change process (i.e. resources/inputs, outcomes, impacts) have been integrated into empirical research. In addition to identifying trends and gaps in the literature, the authors use this information to provide informed recommendations for future research in the area of sport-based PYD.